KEKERASAN DALAM PACARAN PADA RUANG AKADEMIK STUDI KASUS IAIN TULUNGAGUNG - Sari, Dian Kurnia (IAIN Tulungagung, 2018)
The emergence cases of dating violence in the last few decades is increasingly furious of human rights activists. Moreover dating violence cases camuflage in love. Diversity mode of violence had happened make a potrey that emergency condition in our patriarchal society. The cases of dating violence hadi been quoted by National Commision of women increasing from 2015 to 2017 full more than 3000 cases. Unfortunately, violence targeting anyone, include educated society. According to national women’s commision record there are 700 cases happend among students. Reflecting from the case there is a lame over the paradigm of dating. Even in the academic space there are still such deviant practices. Among them, the imagination of courtship, dating orientation and memaknai dating with a patriarchal point of view. To understand how the inequality occurs then the researcher uses qualitative methods, with in-depth and open interviews. Interviews were conducted to five resource persons who had been victims or perpetrators of violence in courtship. The result of the paradigm about dating is influenced by the media that presents a way to relate to the principle of love. In fact there are resource persons who forced his girlfriend to obey the imagination of women like in a movie that he had watched. Cases experienced by resource persons are so diverse. Starting from psychic violence, orientation and even physical. In the eyes of CEDAW the first article explains that any form of gender based violence is not justified in the name of human rights. Therefore, forms of violence based on love are time to end by educating the introduction of a healthy courtship. Either through institution or one by one. Keyword: Relationship, Dating Violence, Human Right Violations